2016
DOI: 10.1093/annonc/mdw152
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling of anal squamous cell carcinoma reveals distinct genomically defined classes

Abstract: This is the first comprehensive genomic analysis of ASCC, and the results suggest new therapeutic approaches. Differing genomic profiles between HPV-associated and HPV-negative ASCC warrants further investigation and may require novel therapeutic and preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 29 publications
13
78
0
2
Order By: Relevance
“…In the combined (pilot plus extension) cohort, 10 of 31 tumors (32%) harbored a PIK3CA mutation, similar to the rate reported in recent targeted sequencing studies. [11, 12] Similarly, the overall mutation frequency of FBXW7 in the pooled cohort (6/31, 19%) is comparable to the rate described in other HPV-associated SCCs. [12]…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…In the combined (pilot plus extension) cohort, 10 of 31 tumors (32%) harbored a PIK3CA mutation, similar to the rate reported in recent targeted sequencing studies. [11, 12] Similarly, the overall mutation frequency of FBXW7 in the pooled cohort (6/31, 19%) is comparable to the rate described in other HPV-associated SCCs. [12]…”
Section: Resultssupporting
confidence: 55%
“…[10] Targeted sequencing of known cancer genes has revealed mutations in EGFR , KRAS , and PIK3CA , and a recent study using a combination of targeted sequencing and immunohistochemistry (IHC) revealed high levels of EGFR expression and frequent mutations in the PIK3CA/AKT pathway. [11-13] However, no exome-wide mutational studies are available and the impact of CRT on genomic evolution is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly mutated gene was PIK3CA (33% samples) with TP53 second most frequent in 15%. Further evidence of the high frequency of these mutations comes from data (using a 236 gene NGS panel) from 70 anal cancers (Chung et al , 2016). In total, 87% were HPV positive.…”
Section: Molecular Mechanisms For Differential Sensitivity To Crt Inmentioning
confidence: 99%
“…Specifically in anal cancer, there is evidence that EGFR is overexpressed, and is independent of gene amplification (11). Moreover, KRAS and BRAF mutations appear rare in these tumors, supporting a role for EGFR inhibitor therapies, since these therapies have not shown benefit in patients with mutant tumors (1218). These observations suggest that the addition of EGFR inhibition to CRT has potential for clinical benefit for patients with anal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that the addition of EGFR inhibition to CRT has potential for clinical benefit for patients with anal cancer. There is evidence of clinical benefit in treating metastatic anal cancer patients with cetuximab alone or in combination with irinotecan, even in patients who are heavily pre-treated (18). Unfortunately, recent clinical trials using cetuximab have shown significant toxicity when combined with conventional CRT for patients with anal cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%